French-German Interest Rate Differentials and Time-Varying Realignment Risk - Caramazza, Francesco (IMF Working Papers; Working Paper ;, 1993)
This paper explores the determinants of expected rates of realignment of the French franc/Deutsche mark exchange rate during the period 1987-1991. It does so by first estimating expected parity changes and then relating these to economic variables that are believed to influence agents' realignment expectations. Time-varying expected rates of realignment are estimated in two ways: one, by adjusting short-term euromarket interest rate differentials for the expected rate of change of the FF/DM exchange rate within the EMS fluctuation band and two, by the differential in the yield on long-term government bonds. The behavior of the exchange rate within the band is found to be consistent with mean reversion and the expected change is nontrivial. Thus, by filtering out the expected mean reversion within the band from short-term interest rate differentials more precise measures of expected changes in the central parity are obtained. Realignment expectations are found to be closely related to the evolution of fundamental economic variables and, for shorter horizons, the position of the franc in the fluctuation band.